Dampak Pandemi Covid-19 Terhadap Manajemen Perubahan Dan Inovasi - Nafis, Fadly Abdillah; Aslami, Nuri (Jurnal Manajemen Akuntansi (JUMSI), 2022)
When the industrial revolution 4.0 necessitated a paradigm shift in management, eachcorporate organization was obliged to restructure its management and operations. When itcomes to the COVID-19 epidemic, numerous government restrictions, including thosegoverning working, learning, and praying from home, are referred to as work from home.Leadership has shifted away from face-to-face meetings between leaders and employees andis now compelled to work online from home. The majority of businesses may adapt by optingto conduct business online. One of the catalysts for the economic crisis, but the mostpronounced, is layoffs or layoffs in the service industry. Due to the prevalence of social andeconomic inequality in society, both individuals and work relationships, both leaders andsubordinates must be able to collaborate to address the COVID-19 Pandemic problem andfind a solution. This study employs a qualitative approach to shed light on management shiftsduring the COVID-19 pandemic. The study is based on published research on changemanagement during the COVID-19 pandemic.